2007
DOI: 10.1161/circulationaha.106.684795
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Dependent Degradation of Guanosine 5′-Triphosphate Cyclohydrolase I Causes Tetrahydrobiopterin Deficiency in Diabetes Mellitus

Abstract: Background-Tetrahydrobiopterin (BH4) deficiency is reported to uncouple the enzymatic activity of endothelial nitric oxide synthase in diabetes mellitus. The mechanism by which diabetes actually leads to BH4 deficiency remains elusive. Here, we demonstrate that diabetes reduced BH4 by increasing 26S proteasome-dependent degradation of guanosine 5Ј-triphosphate cyclohydrolase I (GTPCH), a rate-limiting enzyme in the synthesis of BH4, in parallel with increased formation of both superoxide and peroxynitrite (ONO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
160
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 48 publications
(58 reference statements)
14
160
0
Order By: Relevance
“…In addition, the resolution of GTPCH1, which is an enzyme involved in the production of BH4, is promoted by proteasome-dependent degradation under the presence of peroxynitrite. 27 Consequently, reduced production of BH4 may induce eNOS uncoupling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the resolution of GTPCH1, which is an enzyme involved in the production of BH4, is promoted by proteasome-dependent degradation under the presence of peroxynitrite. 27 Consequently, reduced production of BH4 may induce eNOS uncoupling.…”
Section: Discussionmentioning
confidence: 99%
“…22 Xu et al reported that proteasome-dependent degradation of GTPCH I was related to endothelial dysfunction in diabetes. 19 Wang et al reported that the inhibition of GTPCH I degradation by AMPK activation attenuated endothelial dysfunction. 23 Our data showed that metformin exerts a protective effect on GEnCs as well as vascular endothelial cells via maintenance of GTPCH I level.…”
Section: Discussionmentioning
confidence: 99%
“…HG activates 26S proteasome, resulting in enhanced degradation of GTPCH I in endothelial cells. 19 We evaluated 26S proteasome activity induced by high glucose stimulation and the effect of metformin. HG significantly increased 26S proteasome activity in human GEnCs.…”
Section: Evaluation Of Biopterin Levels and Enos Dimer/ Monomer Strucmentioning
confidence: 99%
See 2 more Smart Citations